KESEJARAHAN DAN TEMA PUISI PENYAIR PEREMPUAN BANGKALAN - Muhri, Muhri (Jurnal Sastra Aksara, 2018)
This article is motivated by the conditions of Bangkalan poeters who after a long time did not produce female writers, in the fourth generation emerged through the work of five female poets. This presents a research problem question 1) What is the history of women's writing in Bangkalan? and 2) What are the dominant themes raised by the Bangkalan female poet in their poetry? The research method uses two methods, namely descriptive analysis method and content analysis method. From the results of the study, two discussions can be produced in accordance with the research problem. Historically it can be discussed that women's art activists have existed since the third generation. They did not produce enough writing to become a book. Based on the content of the theme, poetry with the theme of love dominates. In general, social themes are also dominant in their writing.